Recent advances in generalized thermoelasticity theory and the modified models: a review. Issue 1 (7th January 2021) - Shakeriaski, Farshad; Ghodrat, Maryam; Escobedo-Diaz, Juan; Behnia, Masud
Abstract: A review of the recent studies on the generalized thermoelasticity theories and their associated modified models is presented. The aim is to outline an overview of the utilization and physical limitations of available relevant theories. By contrast to classical thermoelasticity theory, generalized thermoelasticity theories (second sound) can involve a hyperbolic-form transport correlation and are motivated by experiments illustrating more accurately of the wave-form heat transfer (second sound). Many researchers have formulated such theories on different fields and analyzed various problems, presenting characteristic properties of these theories. This paper expresses a self-included bibliographical review of previous documents in the area of the second sound. The general structure of this review contains theories, formulations, real limitations, and used solution techniques of the equations for different geometries and loadings. Given that the classical theory is feeble in simulating the temperature distribution, especially in the structures under a sudden thermal shock, this review may be a useful tool for researchers who work in sensitive industries such as steam turbines, micro-temperature sensors, and lithium battery manufacturing. Graphical Abstract: